The Effect of Nickel Electroplating Time on Alumunium 2024 to ITS Mechanical Property - Hidayah Fajria; Ferry Setiawan; Dhimas Wicaksono (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of this nickel electroplating research on aluminum is to determine the effect of time on mechanical properties in the form of hardness values from specimens and then the SEM-EDX Test is carried out on specimens with the highest hardness test values to find out the microstructure and composition in the coating. The materials used in this study are nickel as the coating and aluminum 2024 as the coated material. The fixed variables used in this study include voltage (25 V), electrode distance (20 cm), water (2400 ml), salt (40gr), vinegar (1600 ml), aluminum 2024, and nickel. The free variables are variation in coating time, namely 10, 15, and 20 minutes. The results of this study showed that the highest hardness value was found in specimens with 10 minutes of immersion time with a value of 198.31 HV and the lowest in specimens with 20 minutes of immersion time with a value of 132.81 HV. After the SEM-EDX test, it was found that the micro layer structure contained pitting (defects) and the element with the highest presentation in the layer was Ni with a mass of 84.07% and an atomic number of 55.29%.